Emotional intelligence and breast cancer: A systematic review - Morales-Sánchez, Lucía (2024)
Introduction: Emotional Intelligence (EI), defined as the ability to perceive, identify, understand, and regulate emotional states is related to health outcomes. In this line, some studies examined this personal resource in the cancer area and, specifically, in breast cancer. Also, the different models and measures have led to a categorisation considering the various construct-method pairings of EI. Despite the increased number of studies about EI in the breast cancer context, there are no systematic reviews that summarise the results obtained in the different investigations. Objectives: Hence, the present review aims: to identify and describe the measures that have been used for assessing EI within this field, and to summarise the main results regarding EI in terms of its predictors and outcomes, considering the instruments used to assess it. Methods: The PRISMA guidelines were followed. Database search was conducted in WOS, Scopus, Pubmed, and PSYCArticles. Results: A total of 156 articles were found and 21 met the eligibility criteria. On one hand, one of the most used instruments was the TMMS-24 framed within the self-report ability EI, followed by those framed within the self-report mixed EI. None of the studies measured EI by the performance-based ability EI perspective. On the other hand, EI was related to other variables such as psychological well-being, quality of life, resilience, workability, anxiety, and depression. The majority of the studies were cross-sectional, and some of them included an intervention. Conclusions: This review provides a comprehensive overview of the existing studies concerning EI in the context of breast cancer, highlighting some of its characteristics regarding design, participants, used measures, and related variables. Also, the obtained results can improve the clinical practice and the understanding of the EI as an influencing factor in the health and quality of life of breast cancer populations.